(untitled) (European Journal of Pure and Applied Mathematics, 2019)
In this paper, it is a question of identification of the parameters in the equation of Richards modelling the flow in unsaturated porous medium. The mixed formulation pressure head-moisture content has been used. The direct problem was solved using Multiquadratic Radial Basis Function ( RBF-MQ ) method which is a meshless method. The Newton-Raphson’s method was used to linearize the equation. The function cost used is built by using the infiltration. The optimization method used is a meta-heuristic called Modified hybrid Grey Wolf Optimizer -Genetic Algorithm (HmGWOGA). A test on experimental data has been carried. We compared the results with genetic algorithms. The results showed that this new method was better than genetic algorithms.